La musica si infiltra nella poesia – l’arte di Eugenio Montale - Mohácsy, Eszter (Verbum – Analecta Neolatina, 2017)
This study discusses the connection between music and poetry in the early period of the Italian Nobel prize winner, Eugenio Montale’s poems. The greatest musical influence on his way of writing was the French composer, Claude Debussy. In this paper, I show how Montale was able to use this influence in certain poems. The paper focuses on three different pieces (Corno inglese, Falsetto, Musica sognata) of the same volume, Ossi di seppia. With few quotes from the poet himself, the reader will have a closer understanding of the essence of Montale’s poetry and how music can be the focus and not only an instrument in these poems.